2008
DOI: 10.1055/s-2008-1063566
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Nasal Dorsal Augmentation

Abstract: Structural deficiencies of the nasal dorsum most commonly derive from congenital, traumatic, and iatrogenic etiologies. Alternatively, dorsal deficiency may be a manifestation of a generally underprojected nose with otherwise appropriate relationships between the radix, dorsum, and tip. In analyzing dorsal deficiency, associated anatomic abnormalities leading to compromise of both aesthetic form and respiratory function must be recognized and incorporated into the reconstructive plan. The cornerstone of augmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Due to these characteristics, the implant firmly adheres to the surrounding tissues and prevents migration. It can fill or contour a defect, but it provides little structure at the implant site 3 . In a multicenter, retrospective study on 309 patients who underwent dorsal nasal augmentation with Gore-Tex implants, 3.2% of the implants were infected in the patients with nasal septal perforation 36 .…”
Section: Mersilene ® (High Density Polyethylene)mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to these characteristics, the implant firmly adheres to the surrounding tissues and prevents migration. It can fill or contour a defect, but it provides little structure at the implant site 3 . In a multicenter, retrospective study on 309 patients who underwent dorsal nasal augmentation with Gore-Tex implants, 3.2% of the implants were infected in the patients with nasal septal perforation 36 .…”
Section: Mersilene ® (High Density Polyethylene)mentioning
confidence: 99%
“…The ideal alloplast must be chemically inert, biocompatible 3 , not physically modified by soft tissue; it should elicit no chronic inflammatory reaction or foreign body reaction, integrate into soft tissue or bone, resist mechanical strains. The site of implantation must meet the following conditions: no infection, no poor soft-tissue coverage, no poor blood supply from scarring, no history of radiotherapy, no soft-tissue tension 2 .…”
Section: The Ideal Biomaterials For Nasal Reconstructive Surgerymentioning
confidence: 99%
“…Achieving a symmetric, smooth, stable, and desired nasal dorsum that fulfills the criteria of adequate form, function, and patient expectation remains a principle challenge during primary or secondary rhinoplasties. [1] Though alloplastic implants provided a good alternative, a good number of patients developed complications including thinning of the skin over the implant, extrusion, infection, displacement, translucency of the implant, and chronic pain. Although such treatment initially caused increase in dorsal nasal height and projection, sustaining this over a time period was not feasible.…”
Section: Introductionmentioning
confidence: 99%
“…[23] It is reported that with proper carving and meticulous construction, augmentation rhinoplasty using costochondral material can produce excellent results. [13]…”
Section: Introductionmentioning
confidence: 99%
“…32 This complication is more common with alloplastic implants than autografts. 14 The postoperative infections most often remain localized to the skin and subcutaneous tissues of the nose but occasionally extend intracranially or result in generalized septicemia. 32 MR imaging or CT can be used to delineate the extent of infections, which can appear as fluid collections, sclerosis and enhancement of osseous structures, and soft-tissue inflammatory changes (Fig 11).…”
Section: Complicationsmentioning
confidence: 99%